2019
DOI: 10.1103/physrevfluids.4.071501
|View full text |Cite
|
Sign up to set email alerts
|

Heat transfer in rough-wall turbulent thermal convection in the ultimate regime

Abstract: Heat and momentum transfer in wall-bounded turbulent flow, coupled with the effects of wallroughness, is one of the outstanding questions in turbulence research. In the standard Rayleigh-Bénard problem for natural thermal convection, it is notoriously difficult to reach the so-called ultimate regime in which the near-wall boundary layers are turbulent. Following the analyses proposed by Kraichnan [Phys. Fluids 5, 1374-1389(1962] and Grossmann & Lohse [Phys. Fluids 23, 045108 (2011)], we instead utilize recent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 67 publications
0
11
0
Order By: Relevance
“…2017; MacDonald et al. 2019; Emran & Shishkina 2020) further revealed that at height the exponent decreases back to the exponent in the smooth cell, due to the competition between the turbulent bulk and BL flow.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…2017; MacDonald et al. 2019; Emran & Shishkina 2020) further revealed that at height the exponent decreases back to the exponent in the smooth cell, due to the competition between the turbulent bulk and BL flow.…”
Section: Introductionmentioning
confidence: 96%
“…With sinusoidally rough upper and lower surfaces in two dimensions, Toppaladoddi, Succi & Wettlaufer (2015 numerically showed that the Nu(Ra) scaling exponent reaches the value of 0.5 for a certain roughness wavelength. Recent studies (Zhu et al 2017;MacDonald et al 2019;Emran & Shishkina 2020) further revealed that at height Ra the Nu(Ra) exponent decreases back to the exponent in the smooth cell, due to the competition between the turbulent bulk and BL flow.…”
Section: Introductionmentioning
confidence: 99%
“…2017, 2019; MacDonald et al. 2019; Tummers & Steunebrink 2019). This transient scaling would not imply the transition to the asymptotic ultimate scaling, because a further increase in leads to saturation down to the classical scaling .…”
Section: Introductionmentioning
confidence: 99%
“…As an example, the introduction of wall roughness has been widely adopted to disrupt boundary layers by enhancing the detachment of the thermal boundary layer from the tips of rough elements (8)(9)(10)(11). As the analog to pressure drag is absent in the temperature advection equation (18), however, the system settles back to the boundary-layer-controlled regime for large imposed temperature differences (9,12). Another attempt is to perform the lateral confinement of turbulent flows (14,15), which has been successful in manipulating the flow structures in the convective bulk, yet the laminar boundary layers still limit the global heat flux.…”
Section: Introductionmentioning
confidence: 99%